Startup life :surviving and thriving in a relationship with an entrepreneur /Brad Feld, Amy Batchelor. - Feld, Brad.
Real life insights on what it takes to make it in a relationship with an entrepreneur Entrepreneurs are always on the go, looking for the next ""startup"" challenge. And while they lead very intensely rewarding lives, time is always short and relationships are often long-distant and stressed because of extended periods apart. Coping with these, and other obstacles, are critical if an entrepreneur and their partner intend on staying together-and staying happy. In Startup Life, Brad Feld-a Boulder, Colorado-based entrepreneur turned-venture capitalist-shares his own personal ex.